2017
DOI: 10.3390/su9020204
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Mechanisms behind Changing People’s Recycling Behavior at Work by Applying a Comprehensive Action Determination Model

Abstract: Abstract:This study moves toward a better understanding of the mechanisms behind changing people's recycling behavior at work by mapping out which pathways and variables change in recycling behavior as triggered by interventions. A questionnaire was designed based on the theory of planned behaviour, the norm-activation model, habits, and a comprehensive action determination model (CADM). The data was collected in two rounds: before the intervention and after a three-month pilot period with implemented interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
1
22

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 37 publications
11
84
1
22
Order By: Relevance
“…We also found that social norms influenced socially responsible buying behaviours both directly and indirectly through personal norms. These findings corroborate prior research in the proenvironmental domain (e.g., Farrow et al, 2017;Ofstad et al, 2017).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…We also found that social norms influenced socially responsible buying behaviours both directly and indirectly through personal norms. These findings corroborate prior research in the proenvironmental domain (e.g., Farrow et al, 2017;Ofstad et al, 2017).…”
Section: Resultssupporting
confidence: 91%
“…Previous research has suggested that social norms partly become internalised-that is, translated into personal norms (Schwartz, 1977;Wenzel, 2004). The literature also offers empirical evidence of a positive relationship between the two types of norms in the context of consumers' recycling behaviour (Ofstad, Tobolova, Nayum, & Klöckner, 2017), leading to the following hypothesis:…”
Section: Relationships Between the Variables Within The Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For behavioral change to be effective, the new behavior has to be repeated in a stable context over time ( Klöckner and Matthies, 2012 ). The comprehensive action determination model (CADM) ( Klöckner and Blöbaum, 2010 ) has been used and applied across behavioral domains to measure habit strength (e.g., Ofstad et al, 2017 ; Joanes et al, 2020 ). Aligning with the Theory of Planned Behavior (TPB) ( Ajzen, 1991 ), the model postulates that individual environmentally relevant behavior is determined directly by intentions and perceived behavioral control and integrates habit strength as the third predictor of behavior.…”
Section: Discussionmentioning
confidence: 99%
“…For each context, respondents answered five semantic differential scales adapted from Ofstad, Tobolova, Nayum, and Klöckner [61] to measure attitudes toward recycling. Response options ranged from 1 to 7, with a higher score representing a more positive attitude (M = 5.93, SD = 1.38, Cronbach's α = 0.96).…”
Section: Attitude Toward Recyclingmentioning
confidence: 99%